QARAQALPAQ TILINDE KÓZ SOMATIZIMI - Umarova, Ú.A. (ILIM hám JÁMIYET, 2025)
This article uses proverbs and sayings from Karakalpak folklore using the somatism "Eye" as the main basis. It discusses proverbs and sayings rich in paremiology, concepts, and their specific characteristics.